Strategy Development for Lean Manufacturing Implementation in Production Shop - Dharmender (My University, 2007)
The technology during the 21st century offers a great promise to the people all over the world. The latest advances in Engineering Science and technology have given engineers powerful tools for re-assessing and reorganizing the systems. In the present business scenario, competitiveness of manufacturing companies is determined by their ability to meet and respond as swiftly as possible to the changing environment scenario and to produce and supply high-quality products at lower cost as per demand of the customer. All the manufacturing companies are striving too hard to achieve their aims, objectives and their capabilities by proper planning and skillfulness, through application of automation and innovative concepts, e.g. lean manufacturing, just-in-time (JIT), and total quality management (TQM). Among these innovative concepts, lean manufacturing is recognized by the manufacturing companies as a major driver to achieve world-class capabilities. Many large and medium-size manufacturing companies have adopted lean manufacturing concepts, and experienced reduction in manufacturing lead time and material handling cost, and improvement in quality with other benefits. It is generally agreed that for a lean manufacturing programme to be effective, it should include a set of tools and techniques or provisions to ensure management commitment, employee involvement, identification of wastes, development of controls for wastes and training and education for employees. These tools and techniques are said to be typical of any comprehensive lean manufacturing implementation programme. The implementation of lean manufacturing reduced the waste in the industry and enhances the profit and production. The present study has been undertaken for analyzing different types of wastes in a Diesel Locomotive Plant’s Light Machine Shop (camshaft section) with an aim to design strategies for developing and implementing a Lean Manufacturing Program in such machine shops. The study has been carried out in a phased manner. Various phases of the study have been: clarifying the context through a review of literature; understanding and assessing the current status of in the organization and identifying the areas which need to be taken up for further, detailed analysis of wastes and aligning them to Lean Manufacturing principles. The different types of wastes that have been identified for detailed analysis after the preliminary study are (1) Defects, (2) Inventory, (3) Excessive Material Movement, (4) Delay due to Waiting, (5) Overproduction and (6) Inappropriate processing. After the analysis, the job needing redesign to reduce the waste have been identified and then by using the cause and effect diagram, the root causes of problems relating to wastes have been identified. Appropriate controls for the identified causes have been developed for each waste and its impact on implementation of Lean Manufacturing principles has been listed. For the purpose of modeling for developing a strategy for implementation, the controls identified have been grouped into broad generalized categories. Expert opinion has been utilized to identify factors and parameters affecting development of a generalized approach for implementation. Generalized of various measures for developing an approach to be used by industry in future has been suggested using expert opinion. It has further been suggested that the implementation of the development approach be carried out in three phases.
Keywords: Strategy Development; Light Machine Shop; Lean Manufacturing Principles; Cellular Manufacturing